The Effect of Magneto-Priming on the Physiological Quality of Soybean Seeds - de Faria, Rute Q.; dos Santos, Amanda R. P.; Batista, Thiago B. [UNESP]; Gariepy, Yvan; da Silva, Edvaldo A. A. [UNESP]; Sartori, Maria M. P. [UNESP]; Raghavan, Vijaya (MDPI, 2023)
Microwaves have been applied to the drying of seeds of several species due to their maintenance of the quality of the seeds and reduction of time and costs. However, few is known about the effect of microwaves on the increase of the physiological quality of soybean seeds and especially their effects on longevity. Therefore, the use of microwaves as magneto-priming in soybean seeds was the object of study in this work. For this purpose, two soybean cultivars were selected and submitted to the ultra-high frequency (UHF) microwave exposure of 2.45 GHz, in the wavelength of 11 cm, and power of 0.2 W/g, for 15 min. The results showed that this condition of exposure to the microwave brought benefits in both cultivars after treatment. Incremental improvements were observed in the germinability indexes, the seedling length, the water absorption by the seeds, the fresh mass, dry mass, and longevity. The genes related to seed germination and longevity showed superior expression (HSFA3, HSP21, HSP17.6b, EXP, ABI3) with magneto-priming treatment. The data found ensure the use of the technique as a viable option for pre-treatment as magneto-priming in soybean seeds in order to improve seed quality.
Keywords: drying modelling; electromagnetic bio stimulation; P50; seed survival; ultra-high frequency; wavelength